Impaired wound healing is associated with poorer mood and reduced perceived immune fitness during the COVID‐19 pandemic: A retrospective survey. Issue 5 (8th August 2022) - Balikji, Jessica; Kiani, Pantea; Hendriksen, Pauline A.; Hoogbergen, Maarten M.; Garssen, Johan; Verster, Joris C.
Abstract: Background and Aims: The coronavirus disease‐2019 (COVID‐19) pandemic disrupted medical care of patients with chronic wounds, and in combination with other negative effects of lockdown measures, this may have a negative effect on mood and quality of life. Until now, the consequences of the COVID‐19 pandemic and associated lockdowns for individuals with impaired wound healing have not been investigated. Methods: An online survey was conducted to evaluate perceived immune fitness, mood, and health, both before and during the COVID‐19 pandemic. Results: Of the 331 Dutch pharmacy students that completed the survey, N  = 42 participants reported slow healing wounds and/or wound infection and were allocated to the impaired wound healing group; the other N  = 289 participants served as control group. The survey assessed mood, perceived immune fitness, and health correlates for (a) the year 2019 (the period before the lockdown), (b) the first lockdown period (March 15–May 11, 2020), (c) summer 2020 (no lockdown), and (d) the second lockdown (November 2020–April 2021). The analysis revealed that negative mood effects, reductions in quality of life, and perceived immune fitness during the two lockdowns were significantly more pronounced among individuals that reported impaired wound healing compared to the control group. The effects on mood, perceived immune fitness, and health correlates were most pronounced for the second lockdown period. Conclusion: The COVID‐19 pandemic is associated with significantly poorer mood, quality of life, and reduced perceived immune fitness. These effects are significantly more pronounced among individuals with self‐reported impaired wound healing.